In search of intangible connections: intellectual capital, performance and quality of life in higher education institutions - Pedro, Eugénia de Matos (2020)
This study explores the contributions of different dimensions of the intellectual capital of higher education institutions (ICHEIs) to their performance, incorporating the previously unexplored dimension of quality of life (QoL) as a performance measure, and correspondingly taking into account the connection between the Theory of Stakeholders and the Theory of Legitimacy. Applying a Structural Equation Model and the Partial Least Squares method, we present new empirical findings from a sample of 738 students and 587 lecturers/researchers from seven Portuguese public HEIs. The ICHEIs positively influence the institution's performance, through relational capital and structural capital; and QoL emerges as an important dimension of HEIs' performance standards, especially regarding students' perception of academic QoL. When HEIs understand and measure their IC, they will gain a better understanding of their core competencies, enabling a better allocation of resources and implementation of more effective strategic and operational actions.